Understanding Guilin Tourism Major Students Toward Financial Management Knowledge Courses In The Era Of Knowledge Payment - Zhang Jing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
As internet technology advances, paying for knowledge has become a popular way of learning. This trend has increased the demand for financial management courses among non-financial majors, such as tourism. With Guilin's geographical advantage, many students in the area are pursuing non-financial tourism majors. Therefore, it is crucial to conduct extensive research on this group's willingness to purchase financial management courses, an essential and valuable topic. The knowledge payment market is developing rapidly. Understanding the purchasing intentions of non-financial tourism majors will help grasp market trends and provide market development directions for relevant institutions. The number of respondents for this study was 380. The results of this study show that students’ purchase intention on management courses for their career development would be impacted by performance expectation, effort expectation, and social impact.